Schizophrenia and Sex Hormones: What Is the Link? - Brzezinski-Sinai, Noa A.; Brzezinski, Amnon (Frontiers in Psychiatry, 2020)
The involvement of gonadal hormones in the pathogenesis of schizophrenia has long been suspected because the psychosis differs in women and men and the illness first makes its appearance shortly after puberty. Changes in sex hormones have been linked with increased vulnerability to mood disorders in women, while testosterone have been associated with increased sexual drive and aggressiveness in men as well as women. Some studies have found abnormal levels of estrogens and testosterone in schizophrenia patients, but the results have been inconsistent and sometimes attributed to the hyperprolactinemia effect of antipsychotics, which may interfere with sex hormones production. The purpose of this review is to present the current knowledge on the link between blood levels of sex-hormones in women during the various stages of the female reproductive life (i.e. puberty, menstrual cycle, pregnancy, contraception, and menopause) and the course of schizophrenia. We also attempt to optimize the clinical approach to women with schizophrenia at these different stages.